Pre- and Post-Operative Intraocular Pressure of Pediatric Cataract Surgery - Reyhana Khansa Mawardi; Dicky Hermawan; Kristanti Wanito Wigati; Rozalina Loebis (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2022)
Introduction: Cataract is an eye lens opacification which prevents clear vision. It is the leading cause of blindness and vision impairment worldwide, including Indonesia. It can also be occurred in children that leads to a major cause of childhood blindness. The prevalence of childhood cataract ranges from 3 to 6 per 10,000 children. The main treatment for cataract is surgery, although pediatric cataract surgery has several complications. One of the most severe complication is glaucoma due to increased intraocular pressure (IOP). This study aimed to determine pre- and post-operative IOP in pediatric cataract surgery.Methods: This was a cross-sectional observational analytic study. Secondary data were collected from medical records of Department of Ophthalmology, Dr. Soetomo General Hospital Surabaya from January 2017 to August 2019. Age, gender, pre- and post-operative IOP, and intraocular lens implantation data were taken. Calculation was performed using the Saphiro-Wilk for data less than 50 samples. The Saphiro-Wilk test results showed that the data were normally distributed (p = 0.628). Data processing were then performed using the parametric t-pair test with a confidence level ofResults: 32 eye samples were obtained from 16 pediatric cataract surgery patients. The mean of pre-operative IOP was 13.05 mmHg and the mean of post-operative IOP was 13.36 mmHg. There was an increase in post-operative IOP with an average increase of 0.31 mmHg. There was no significant difference between pre- and post-operative IOP of pediatric cataract surgery patients (p = 0.711).Conclusion: There was no difference between pre- and post-operative IOP of pediatric cataract surgery patients at Dr. Soetomo General Hospital Surabaya for the period of January 2017 - August 2019.